2000
DOI: 10.1080/10556780008805795
|View full text |Cite
|
Sign up to set email alerts
|

A multigrid approach to discretized optimization problems

Abstract: Many large optimization problems represent a family of models of varying size, corresponding to different discretizations. An example is optimal control problems where the solution is a function that is approximated by its values at finitely many points. We discuss optimization techniques suitable for nonlinear programs of this type, with an emphasis on algorithms that guarantee global convergence. The goal is to exploit the similar structure among the subproblems, using the solutions of smaller subproblems to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
194
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 134 publications
(194 citation statements)
references
References 17 publications
0
194
0
Order By: Relevance
“…For example the truncated Newton scheme used in [5]. Given an initial approximation x 0 k to the solution of (1), the application of…”
Section: The Mg/opt Methods For Optimizationmentioning
confidence: 99%
See 4 more Smart Citations
“…For example the truncated Newton scheme used in [5]. Given an initial approximation x 0 k to the solution of (1), the application of…”
Section: The Mg/opt Methods For Optimizationmentioning
confidence: 99%
“…This claim appears to be true as far as a line search along the coarse-grid correction is performed. Also in [5] it is reported that MG/OPT without line search diverges in some cases. Therefore line search appears to be necessary for convergence.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations